Alkynyl Sulfonium Salts Can Be Employed as Chalcogen‐Bonding Catalysts and Generate Alkynyl Radicals under Blue‐Light Irradiation - Lu, Yu; Liu, Qiang; Wang, Zhi‐Xiang; Chen, Xiang‐Yu (Angewandte Chemie International Edition, 2022)
Chalcogen bonding (ChB) has emerged as a promising tool in organic synthesis. However, compared with the well‐developed selenium‐ and tellurium‐based salt catalysts, the ChB catalysis of sulfonium salts is still unknown. Here, we report a new type of alkynyl‐sulfonium salt ChB catalysis for various ionic transformations, including transfer hydrogenation, bromination, bromolactonization, dimerization of 1,1‐diphenylethylene, nitro‐Michael addition reaction and Ritter reaction. More importantly, the photocapability of ChB was first demonstrated to generate alkynyl radicals for the synthesis of a variety of chalcogenoacetylenes. Mechanistic studies shed light on the mechanism of the photoinduced reactions and confirmed the involvement of alkynyl radicals which are difficult to generate otherwise. Alkynyl sulfonium salts were employed as chalcogen bonding (ChB) catalysts for the first time. They display superior capability in the generation of alkynyl radicals under blue‐light irradiation.